Gerakan Peduli Mitigasi Bencana (Penghijauan: Penanaman Bibit Pohon) - Wahyu Lestary; Jernianti Agustina Manurung; Dewi Marta Sari; Jefryanda Jefryanda; Desy Desy; Sindi Suci Ramadanti; Caroline Ayu Ningsih; Putri Nurhayati; Rizky Cahya Wiguna; Samuel Raja Gukguk (LP2M Universitas Muhammadiyah Enrekang, 2023)
KUKERTA is a community service activity in a particular area or educational institution, carried out in groups, integrated between departments, coordinated at the university level. KUKERTA (Real Work Lecture) activities aim to provide real work experience in the field so as to form an attitude of independence and responsibility in carrying out work in the field. In addition, Community Service Program also aims to assist the community in increasing the level of knowledge and skills so that it is expected to improve their welfare. KUKERTA activities are divided into four stages of activities, namely debriefing, implementing activities on site, preparing reports, and evaluating. The implementation of this KUKERTA began on July 10 2023 until August 19 2023 in Meranti Village, Pangkalan Kuras District, Pelalawan Regency. The work program in Meranti Village is a program that emphasizes community empowerment. The physical programs of the Meranti Village KUKERTA group include: Disaster mitigation care movement program (Reforestation: Planting tree seeds), digital literacy education program, dance arts program, and village assistance program. The non-physical program that is carried out is the implementation of In general, KUKERTA cares about disaster mitigation (planting tree seeds), KUKERTA activities in Meranti Village are going very well